'You need to be flexible normally, and here, even more flexible': teaching academics' experiences and perceptions of Covid-19 disruptions to teaching, learning, and assessment. Issue 2 (7th February 2023) - Thomas, Melissah; Yager, Zali; Widdop Quinton, Helen
ABSTRACT: Alongside unprecedented shifts in health care, and widespread lockdowns and stay-at-home orders, the Covid-19 pandemic brought an almost immediate shift towards digitally supported remote delivery in higher education. This paper explores the experiences and perceptions of 15 teaching academics from five universities in Victoria, Australia during this time. Semi-structured interviews were conducted with academics after they had been delivering teaching, learning and assessment remotely for a six-month period. The analysis showed that while the remote delivery environment enhanced many aspects of teaching and learning, including agile and adaptable academic skill-sets, there were challenges. The academics' sophisticated teaching skills and experience, that were intuitively relied upon in the face-to-face setting, did not always translate to the online environment. In particular, this was noticed in terms of the relational approach to teaching and learning, including relationships, rapport, and connectedness within classes, and the absence of social formative assessment cues to evaluate learners' understandings. Students were not asking questions in class and required additional support from academics, which subsequently increased already overburdened workloads. After considering the findings of our work and others, we provide recommendations to support high quality teaching and learning in digitally supported remote delivery.